Public Corruption - Villoria, Manuel (EUNOMÍA. Revista en Cultura de la Legalidad, 2014)
This works analyzes the concept of corruption from different perspectives: law, economy, political science, ethics and sociology. It summarizes the different approaches and creates a typology. Finally, it gives an overview of the most important research challenges in this field.
Keywords: Regulatory and policy capture; principal-agent theory; grand corruption; petty corruption; black, grey and white corruption